Internal defects and water absorption behavior of environmentally friendly brick-MAB using film neutron radiography technique - Alam, MK; Islam, MR; Saha, S; Islam, MN; Islam, SM Azaharul (Journal of Bangladesh Academy of Sciences, 2014)
Film neutron radiography (NR) technique has been adopted to study the internal defects likehomogeneity, porosity, incremental intrusion area, initial rapid absorption (IRA) and water penetratingheight/behavior of the automated machine made environmentally friendly brick-MAB sample.Thermal neutron radiography facility installed at the tangential beam port of 3 MW TRIGA MARK-IIreactor was used in this study. In here optical density or gray values of the neutron radiographicimages of the sample was measured. From the measurement it was found that most of the areas of thissample were homogeneous, which indicateed the presence of a little bit internal porosity andabsorption of water to be very poor. It also showed that its initial rapid absorption was less and waterabsorption behavior was capillary and of wave shape. DOI: http://dx.doi.org/10.3329/jbas.v38i1.20197 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 1-6, 2014